Exploring the Challenges of Reading Comprehension Teaching for English Proficiency Test Preparation Class in Indonesia - Laode Muhammad Firman Guntur; Sadegh Pordanjani Rahimi (ELS Journal on Interdisciplinary Studies in Humanities, 2019)
As one of the tested skills within popular English proficiency tests in Indonesia such as IELTS and TOEFL, good command of reading comprehension skill is pivotal for the test takers. The nature of reading skill in testing circumstances, however, demands precision in decision making. Enabling test taker candidates with such precision in test preparation class, then, dictates the teaching of the skill consequently. This paper discusses the commonly found challenges in teaching the skill for the test preparation class with known diverse students age and background. The primary aim of the study is to provide insightful information about those challenges which may, then, contribute to better teaching of the skill. The critical analysis of the relevant literature suggests that the challenges are comprised of three domains: students’ unequal linguistic competence, different level of students’ critical thinking, and also their motivation. The paper concludes by re-emphasising the crucial role of pre-test for the test taker candidates prior to commencing the preparation class, especially for instructors to map and to anticipate these challenges with more reflective and equitable teaching approach which is informed by the pre-test result.